2014
DOI: 10.1186/1750-9378-9-18
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of human oncogenic viruses in colon cancer revealed EBV latency in lymphoid infiltrates

Abstract: BackgroundEnvironmental factors may play a role in colon cancer. In this view, several studies investigated tumor samples for the presence of various viral DNA with conflicting results.FindingsWe undertook a systematic DNA analysis of 44 consecutive, prospectively collected primary tumor samples by real time and qualitative PCR for viruses of known or potential oncogenic role in humans, including polyomavirus (JCV, BKV, Merkel cell polyomavirus), HPV, HTLV, HHV-8 and EBV. Negative controls consisted of surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 21 publications
5
52
1
Order By: Relevance
“…The PCR and IHC techniques employed in the current study failed to detect genetic material and protein deriving from the virus under investigation in colorectal carcinoma and control tissues. Our data are consistent with the findings of four other research teams who found no evidence of BKV DNA in a large range of colorectal cancer, adenoma, and normal mucosa samples (Militello et al, 2009;Campello et al, 2010;Fiorina et al, 2014;Ripple et al, 2014). Such contradictions may be explained by false-positive results due to contamination during experimental procedures, the sensitivity of the protocols used, population diversity and sample size variation, and BKV incidence in the geographical area of study.…”
Section: Discussionsupporting
confidence: 90%
“…The PCR and IHC techniques employed in the current study failed to detect genetic material and protein deriving from the virus under investigation in colorectal carcinoma and control tissues. Our data are consistent with the findings of four other research teams who found no evidence of BKV DNA in a large range of colorectal cancer, adenoma, and normal mucosa samples (Militello et al, 2009;Campello et al, 2010;Fiorina et al, 2014;Ripple et al, 2014). Such contradictions may be explained by false-positive results due to contamination during experimental procedures, the sensitivity of the protocols used, population diversity and sample size variation, and BKV incidence in the geographical area of study.…”
Section: Discussionsupporting
confidence: 90%
“…More importantly, we were able to show that E6/E7 onco-proteins of high-risk HPV type 16 convert non-invasive and non-metastatic human cancer cells into invasive and metastatic ones. 27 Regarding the presence of EBV in CRC worldwide, several recent investigations reported that 20-50% of these cancer cases are positive for EBV [28][29][30][31][32] ; however, a small number of studies were unable to detect EBV in colorectal carcinomas but in their infiltrated lymphomas. 33,34 Meanwhile, it is important to emphasize that the presence of EBV in the Middle East region is limited to 2 conflicting studies from Iran, as Tafvizi et al, 32 revealed that 38% (19/50) of human CRC cases are positive for EBV in the Iranian population; however, the second study was unable to detect the presence of EBV in only 15 CRC samples.…”
Section: Discussionmentioning
confidence: 99%
“…For CRCs, EBV infection is detected in 19% to 52% of CRC tissue specimens by polymerase chain reaction (PCR) 27,28. However, in situ hybridization analyses for the detection of EBER1-2 RNAs demonstrated EBVs in infiltrating nonneoplastic lymphoid cells but not in tumor cells, which contrasts with EBV-positive gastric cancers in which EBV in situ hybridization exhibit EBVs in nearly all of the tumor epithelial cells 26,27. Regardless of whether EBV is present in tumor cells or not, there is no relationship between the presence of EBV in cancer tissue specimens and CIMP 28.…”
Section: Cause Of Cimp In Crcs and Their Premalignant Lesionsmentioning
confidence: 99%